Outlaw bikers as organized crime - Blokland, Arie Aart Jan; Lampe, Klaus von; Deuren, Sjoukje van (Routledge studies in organised crime and illegal markets, 2025)
"This volume presents cutting edge research on outlaw bikers and outlaw biker clubs from countries all over the globe and reflects the different ways that academic researchers have approached the outlaw biker phenomenon from the theoretical and methodological vantage point of organized crime research"--